Ali desetletniki v Sloveniji berejo bolje ali slabše od vrstnikov v Evropi? - Doupona, Marjeta (Šolsko polje, 2014)
The average reading achievement in Progress in International Reading Literacy Survey is determined by average achievement of the country's students. Students' achievement is calculated by 5 plausible values according to IRT methodology. PIRLS International Reading achievement is artificially set to 500 points with a standard deviation of 100 points. Since the Coleman Report in 1966, numerous surveys and researches have shown a large impact of socio-economic factors to school and academic achievement. Slovenia participated in Reading Literacy Survey1991, in Progress in International Reading Literacy Survey 2001, 2006 and 2011, and each of these surveys showed relationship between socio-economic factors and reading literacy. Socio-economic factors are often defined in terms of a parents' education and the number of books at home since these two factors seem to be important in all participating countries. The differences in achievement between certain groups of students tend to be extremely high. The differences between boys' and girls' reading literacy achievement is usually one fifth of standard deviation, but the difference in reading literacy achievement between students whose parents have different degrees of education tend to be as big as one standard deviation, and sometime even more. Students in Slovenia who have educated parents have approximately the same reading achievement as their peers in other European countries from similar families (if defined by parents' education) while students whose parents are not well educated tend toread much worse than their European peers from similar families. We wonder why scholars even tend to emphasise gender differences in reading achievement while reading differences between varying social groups remain neglected. Of course, gender aspects play an important role in society, however, big differences between social groups need more attention than they receive at the moment otherwise questions of big social differences will remain unanswered.
Keywords: mednarodne raziskave; PIRLS; preverjanje znanja; branje; bralna pismenost; učenci; osnovne šole